GAS5 promotes glucose metabolism reprogramming and resistance to ferroptosis of endothelial progenitor cells through the miR-495-3p/SIX1 and IGF2BP2/NRF2 dual-regulatory pathways in coronary heart disease: Effect of GAS5 on glucose metabolism reprogramming - Zhong, Ming; Xu, Wenxia; Tang, Biao; Zhao, Qiang; Jiang, Zenan; Liu, Yinfeng (Cellular and Molecular Biology, 2024)
We aimed to explore the potential along with mechanism of lncRNA growth arrest-specific 5 (GAS5) in modulating glucose metabolism and ferroptosis of endothelial progenitor cells (EPCs) in coronary heart disease (CHD). CCK-8, flow cytometry, EdU, colony formation, scratch test as well as transwell assays were implemented to assess cell biological behaviors. Glucose uptake testing, lactic acid production assay, and detection of extracellular acidification rate (EACR) together with oxygen consumption rate (OCR) were used to assess glucose metabolism. Iron, GSH and MDA detection were used to measure ferroptosis. Besides, a series of mechanical experiments were implemented to clarify the modulatory relationship between GAS5 and nuclear factor erythroid 2-related factor 2 (NRF2) as well as sine oculis homeobox 1 (SIX1). We found that GAS5 was down-regulated in CHD patients relative to healthy controls. GAS5 depletion repressed EPCs proliferation, migration along with invasion while elevated cell apoptosis. GAS5 promoted the reprogramming of glucose metabolism and inhibited ferroptosis in EPCs. GAS5 affected glycometabolic reprogramming and ferroptosis resistance through regulating SIX1 and NRF2. On the one hand, GAS5 promoted NRF2 mRNA stability through IGF2BP2. On the other hand, GAS5 regulated the miR-495-3p/SIX1 axis in EPCs. To sum up, GAS5 promotes glucose metabolism reprogramming and resistance to ferroptosis of EPCs through the miR-495-3p/SIX1 and IGF2BP2/NRF2 dual-regulatory pathways in CHD.